Complete mitochondrial genome of Pectocera sp. (Elateridae: Dendrometrinae: Oxynopterini) and its phylogenetic implications. Issue 1 (7th August 2022) - He, Jinwu; Yao, Yuhao; Dong, Zhiwei; Ruan, Yongying; Chang, Zhou; Zhao, Ruoping; Wang, Wen; Li, Xueyan
Abstract: The Elateridae family (click beetles) represents a highly diverse lineage that possesses a specialized clicking mechanism to startle predators. At present, however, phylogenetic relationships, especially among recognized subfamilies, remain contentious. Mitochondrial genomes (mitogenomes) can help resolve previously intractable phylogenetic relationships using morphological or limited molecular data. Here, we report the complete mitogenome of Pectocera sp. (Elateridae: Dendrometrinae: Oxynopterini), which was 15, 962 bp in length and showed a typical gene number and order as most beetle mitogenomes, including 13 protein‐coding genes (PCGs), 22 transfer RNA genes, 2 ribosomal RNA genes, and 1 noncoding control region (AT‐rich region). Comparative genomic analyses showed a high degree of feature similarity among Pectocera sp. and other click beetles. Evolutionary analysis of all PCGs based on the nonsynonymous/synonymous substitution rate ratio ( ω ) indicated that cox1 and atp8 exhibited the lowest and highest evolutionary rates, respectively, and that the evolutionary rates of all PCGs, except for cox3, nad2, and nad3, were lower than the average ω of click beetles. Phylogenetic analyses based on concatenated and coalescent approaches indicated that Pectocera sp. was sister to Campsosternus auratus in the same tribe (Oxynopterini) with high support. This study offers insight into the mitogenomic basis of Pectocera sp. and provides an important data resource for exploring the taxonomy, phylogeny, and evolution of click beetles. Abstract : Complete mitochondrial genome of Pectocera sp. (Elateridae: Dendrometrinae: Oxynopterini) and its phylogenetic implications. The phylogenic tree of click beetles is presented with the species within same subfamilies collapsed. The dorsal view and mitogenome maps are shown on the left. Highlights: The mitogenome of Pectocera sp. (Elateridae: Dendrometrinae: Oxynopterini) was sequenced, annotated, and analyzed, and the results show that the mitogenome is highly conserved in gene number and order as those of most beetle mitogenomes. Comparative genomic analyses showed a high degree of feature similarity among the mitogenomes of Pectocera sp. and other click beetles, such as base composition and AT‐bias. Phylogenetic analyses based on 13 PCGs and two rRNA genes ( rrnS and rrnL ) indicated that Pectocera sp. and Campsosternus auratus were grouped together in Oxynopterini with high support. The findings recovered the monophyly of the four subfamilies (Cardiophorinae, Agrypninae, Elaterinae, and Dendrometrinae), and confirmed the phylogenetic position of Pectocera in the tribe Oxynopterini of Dendrometrinae.